Sootblower Type Long Retractable Problem Analysis At PLTU Banten 2 Labuan PGU - Oetomo, Pandoe Satria; Saefuloh, Iman (Universitas Sultan Ageng Tirtayasa, 2023)
Sootblower is equipment used to clean slagging or fouling attached to the boiler wall or pipe pipes contained in the boiler. Slagging is coal ash attached to the furnace, on the furnace wall and on the superheater and reheater pipes. At PT. PLN Indonesia Power PLTU Banten 2 Labuan PGU has 4 types of Sootblowers, namely, Short Retractable Sootblower, Long Retractable Sootblower, Semi-Long Retractable Sootblower, Helical Retractable Sootblower. In the results of the analysis for maintenance on this sootblower, it routinely carries out Preventive Maintenance activities every week and also applies every day, then if the replacement of spare parts must use those that have SNI.